2018
DOI: 10.1093/gerona/gly046
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Aging-Related Changes in Grip Strength and Cognitive Function in Older Adults: A Systematic Review

Abstract: Future research is urged to expand the study of physical and cognitive associations in old age using a within-person and multi-study integrative approach to evaluate the reliability of longitudinal results with greater emphasis on the magnitude of this association.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
69
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(74 citation statements)
references
References 58 publications
1
69
1
3
Order By: Relevance
“…51 In the second review, Zammit et al opined that while both grip strength and cognitive performance decline with age, evidence for an association between longitudinal rates of change in the variables is limited. 118 Several original studies not included in the aforementioned reviews provide evidence supporting a predictive relationship between grip strength and cognitive decline. The studies include Japanese, Korean, and Italian populations, follow-up periods of 1 to 10 years, and cognitive tests as diverse as the Mini-Mental State Evaluation, Digit Symbol Substitution Test, Clock Drawing Test, and the Clinical Dementia Rating Scale.…”
Section: Grip Strength As a Biomarker Of Future Outcomesmentioning
confidence: 99%
“…51 In the second review, Zammit et al opined that while both grip strength and cognitive performance decline with age, evidence for an association between longitudinal rates of change in the variables is limited. 118 Several original studies not included in the aforementioned reviews provide evidence supporting a predictive relationship between grip strength and cognitive decline. The studies include Japanese, Korean, and Italian populations, follow-up periods of 1 to 10 years, and cognitive tests as diverse as the Mini-Mental State Evaluation, Digit Symbol Substitution Test, Clock Drawing Test, and the Clinical Dementia Rating Scale.…”
Section: Grip Strength As a Biomarker Of Future Outcomesmentioning
confidence: 99%
“…Similarly, other longitudinal studies in older adults have shown that both low hand grip strength and slow gait speed at baseline predict future cognitive decline (9,10). Furthermore, systematic reviews have shown that hand grip strength is positively associated with global cognition and some cognitive subdomains, including episodic memory, visuospatial ability and working memory (11). Finally, hand grip strength changes were more strongly related to mental state (which declines much later), whereas gait speed changes were more strongly related to changes in fluid cognition (which declines as early as midlife) (12).…”
mentioning
confidence: 80%
“…A "common cause" suggests the presence of an underlying mechanism that drives the association between physical and cognitive functions and the simultaneous presence of both impairments. The "common cause hypothesis" stems predominantly from the evidence for a strong correlation between age-related declines in both physical and cognitive functions reported in cross-sectional studies, and rarely from within-subject changes in longitudinal studies (6,11,17). In this regard, a common cause of the ageing process can operate at different physiological levels (12).…”
mentioning
confidence: 99%
“…Muscle loss is another dominant characteristic of elderly (Zammit, Robitaille, Piccinin, Muniz-Terrera, & Hofer, 2018). According to the literature, after attaining the age of 40 and during the whole process of aging, there is a progressive loss of muscle tissue and consequent strength, as well as a loss of muscle quality and effectiveness (Abizanda et al, 2012;Zammit et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Muscle loss is another dominant characteristic of elderly (Zammit, Robitaille, Piccinin, Muniz-Terrera, & Hofer, 2018). According to the literature, after attaining the age of 40 and during the whole process of aging, there is a progressive loss of muscle tissue and consequent strength, as well as a loss of muscle quality and effectiveness (Abizanda et al, 2012;Zammit et al, 2018). The decay of muscle mass and strength in older people has been associated with several adverse occurrences; described a reduction of physical activity and global energy output, leading to higher costs to health care (Abizanda et al, 2012).…”
Section: Introductionmentioning
confidence: 99%